2011
DOI: 10.5194/angeo-29-167-2011
|View full text |Cite
|
Sign up to set email alerts
|

On large plasmoid formation in a global magnetohydrodynamic simulation

Abstract: Abstract. We investigate plasmoid formation in the magnetotail using the global magnetohydrodynamic (MHD) simulation GUMICS-4. Here a plasmoid implies a major reconfiguration of the magnetotail where a part of the tail plasma sheet is ejected downstream, in contrast to small Earthwardpropagating plasmoids. We define a plasmoid based solely on the structure of the closed (connected to the Earth at both ends) magnetic field line region. In this definition a plasmoid is partly separated from the ordinary closed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…This is probably because Guo et al [2011] underestimated the ring current injection by using a relative larger ring current decay time ( τ = 8 hours). Note that, some substorm‐related tail energy sinks are not considered in studying the energy budget, such as escape energy carried by plasmoids and plasma sheet heating [ Baker et al , 1997; Ieda et al , 1998; Honkonen et al , 2011]. Koskinen and Tanskanen [2002] suggested that a scaling parameter of 1.5–2 should be applied to the coupling parameters to account for some substorm‐related tail energy sinks in calculating the energy input from the solar wind to the magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because Guo et al [2011] underestimated the ring current injection by using a relative larger ring current decay time ( τ = 8 hours). Note that, some substorm‐related tail energy sinks are not considered in studying the energy budget, such as escape energy carried by plasmoids and plasma sheet heating [ Baker et al , 1997; Ieda et al , 1998; Honkonen et al , 2011]. Koskinen and Tanskanen [2002] suggested that a scaling parameter of 1.5–2 should be applied to the coupling parameters to account for some substorm‐related tail energy sinks in calculating the energy input from the solar wind to the magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation uses solar wind parameters from the ACE satellite as input and the delay time to the dayside magnetopause of 46 min was estimated by Honkonen et al (2011). Figure 4 top panel shows some selected views from the GUMICS simulation.…”
Section: Polar Cap Boundary and Ionospheric Currentsmentioning
confidence: 99%
“…Hence, although substorms appear to be the most commonly investigated feature in the runs, the time instants include all kinds of solar wind conditions (see, e.g. Honkonen et al, 2011), and hence the results will not only be applicable to substorms. Five of the events occur during Northern Hemisphere winter (December-February), one during spring (March-May), two in summer (July-August), and two during the fall (September-November).…”
Section: Imf B Y Dependence Of Energy Transfermentioning
confidence: 99%